PERILAKU TIDAK MEMILIH DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN REPUBLIK INDONESIA TAHUN 2014 (Studi Kasus Kecamatan Pekanbaru Kota) - Wulandari, Sri; Tinov, M. Y. Tiyas (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Behavior does not choose a conscious decision by someone to not use its voting rights by not attending the polling stations on the implementation of the general election. This study examines the behavior is not picking on people in the District of Pekanbaru City election of the President and Vice President in 2014. The authors are keen to do this research, because in democratic countries, elections or election of President and Vice President is an instrument of the implementation of democracy, but Pekanbaru City Subdistrict Subdistrict society many do not exercise their voting rights in the implementation of the democratic party. The research problems are